Introduction : parenting, polyamory and consensual non-monogamy. Critical and queer perspectives - Klesse, Christian (2022)
This special issue explores key issues regarding the parenting practices within polyamorous and consensually non-monogamous intimate relationships. The contributions are concerned with the stigmatization of child-care practices that deviate from the default of couple-based monogamy, exceed biological definitions of kinship and experiment with new forms of spatial organization beyond shared residence. In this introduction, we highlight key themes of previous research, highlight normative pressures and counter-normative contestations around the themes of exclusivity, gendered parenting roles, relational development framed as intimate growth and a pervasive reproductive futurism. Polyamorous parenting practices negotiate a complex social terrain shaped by social and health policies, law, housing development, creating new avenues for parenting roles, and the (re)organization of care work and the division of labour in child-rearing.